2016
DOI: 10.3892/mco.2016.846
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose intra-arterial neoadjuvant chemotherapy while waiting for radical hysterectomy for stage IB-IIB cervical cancer

Abstract: Abstract. Extended wait time prior to initial surgery may increase patients' anxiety. Therefore, patients may opt to receive other available treatments to inhibit tumor growth until surgery. This retrospective study describes our experience with single-dose intra-arterial neoadjuvant chemotherapy (IANAC) to more effectively utilize the wait time prior to radical hysterectomy. A total of 12 patients with International Federation of Gynecology and Obstetrics stage IB1-IIB cervical cancer were treated with single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…These variations resulted primarily in the number of samples, stage of the disease, the treatment modality, and the accessibility to follow-up. There is no evidence that shows that a longer waiting time affects the overall survival (OS) in the first 5 years [11,18,19]. One study has shown that a wait time to surgery longer than 8 weeks leads to worse OS after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…These variations resulted primarily in the number of samples, stage of the disease, the treatment modality, and the accessibility to follow-up. There is no evidence that shows that a longer waiting time affects the overall survival (OS) in the first 5 years [11,18,19]. One study has shown that a wait time to surgery longer than 8 weeks leads to worse OS after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The intervals of application vary (1,10,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)60). In addition, the way the NACT was applied also varied between intravenous and intraarterial injection (53,(65)(66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…Уменьшение размеров опухоли в ближайшие 1-2 мес объясняется местным химиотерапевтическим воздействием, а также ишемическим некрозом новообразования, однако, по мнению ряда авторов, полного некроза опухоли не происходит, а имеет место лишь частичный некроз [14][15][16][17]. Руководствуясь этим, больным РШМ проведены неоднократные курсы внутриартериальной ХИ.…”
Section: оригинальные статьиunclassified